2022
DOI: 10.1002/ange.202116783
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Exciton Coupling of Merocyanine Nucleoside Dimers by RNA, DNA and GNA Double Helix Conformations

Abstract: Exciton coupling between two or more chromophores in a specific environment is a key mechanism associated with color tuning and modulation of absorption energies. This concept is well exemplified by natural photosynthetic proteins, and can also be achieved in synthetic nucleic acid nanostructures. Here we report the coupling of barbituric acid merocyanine (BAM) nucleoside analogues and show that exciton coupling can be tuned by the double helix conformation. BAM is a nucleobase mimic that was incorporated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This finding is in stark contrast to typical models in which disorder associated with a heterogeneous environment reduces the efficiency of exciton transport and points to the scaffold flexibility as an underutilized parameter in excitonic systems. Furthermore, this highlights the role of the DNA scaffold in explicitly mediating excited-state phenomena across time scales, which has since been extended to higher-order architectures and nondeoxy ribosomal nucleic acids. …”
Section: Engineering Couplings For Exciton Transportmentioning
confidence: 95%
“…This finding is in stark contrast to typical models in which disorder associated with a heterogeneous environment reduces the efficiency of exciton transport and points to the scaffold flexibility as an underutilized parameter in excitonic systems. Furthermore, this highlights the role of the DNA scaffold in explicitly mediating excited-state phenomena across time scales, which has since been extended to higher-order architectures and nondeoxy ribosomal nucleic acids. …”
Section: Engineering Couplings For Exciton Transportmentioning
confidence: 95%
“…Although GNA cannot form a natural double helix structure like DNA or RNA, it is capable of forming a stable helix when hybridized to complementary DNA or RNA sequences. Importantly, Alnylam successfully applied and conceptually validated this in several of investigational therapies because of that the addition of GNA has the ability to maintain the specificity of RNAi binding to its target while reducing its binding capacity to off-target sites, further enhancing the specificity and safety of. For instance, Schlegel et al reported that GNA can form stable duplexes with DNA and RNA.…”
Section: Chemical Modification On Rna Therapeutics In Recent Researchmentioning
confidence: 99%
“…As schematically shown in Figure A, when two organic chromophores are in close proximity and have torsional orientation between each other, Davydov splitting would occur due to the Coulombic couplings between their electronic transition dipoles, and hence produce characteristic bisignate CD signals . The coupling strength is determined by the relative orientation and interdistance between the two chromophores and can be approximated as V 12 = μ 1 μ 2 r 12 3 [ e 1 · e 2 3 false( e 1 0em true⃗ · e 12 0em true⃗ false) false( e 2 0em true⃗ · e 12 0em true⃗ false) ] where μ 1 and μ 2 represents the respective transition dipole moment, r 12 0em true⃗ denotes the interseparation between these dipoles, and e⃗ signifies the corresponding unit vectors.…”
mentioning
confidence: 99%